Using a Process Knowledge Based CAD for a More Robust Response to Demands for Quotation - Toussaint, L.; Gomes, S.; Sagot, J. C. (Cranfield University Press, 2009)
Out of 100 hours of engineering work, only 20 are dedicated to real engineering and 80 are spent on what is considered routine work. To accelerate these routine processes, our research is based on methods and tools to capitalize and reuse knowledge in collaborative conception. To validate our research hypotheses, a series of experiments through a design process, with the aid of a Product Lifecycle Management (PLM) tool and a geometric modeler, have been implemented. This article defines a methodology for design and verification of a concept through the use of a knowledge capitalization and its application.
Organised by: Cranfield University
Keywords: Concurrent engineering; design for manufacturing (DFM); knowledge capitalization